A New α + β Ti-15Nb Alloy with Low Elastic Modulus: Characterization and In Vitro Evaluation on Osteogenic Phenotype - Donato, Tatiani Ayako Goto [UNESP]; Sousa, Karolyne dos Santos Jorge [UNESP]; Kuroda, Pedro Akira Bazaglia [UNESP]; Grandini, Carlos Roberto [UNESP] (MDPI, 2023)
This study aimed to produce Ti-15Nb alloy with a low elastic modulus, verify its biocompatibility, and determine whether the alloy indirectly influences cellular viability and morphology, as well as the development of the osteogenic phenotype in cells cultured for 2, 3, and 7 days derived from rat calvarias. Two heat treatments were performed to modify the mechanical properties of the alloy where the Ti-15Nb alloy was heated to 1000 °C followed by slow (−5 °C/min) (SC) and rapid cooling (RC). The results of structural and microstructural characterization (XRD and optical images) showed that the Ti-15Nb alloy was of the α + β type, with slow cooling promoting the formation of the α phase and rapid cooling the formation of the β phase, altering the values for the hardness and elastic modulus. Generally, a more significant amount of the α phase in the Ti-15Nb alloy increased the elastic modulus value but decreased the microhardness value. After the RC treatment, the results demonstrated that the Ti-15Nb alloy did not present cytotoxic effects on the osteogenic cells. In addition, we did not find variations in the cell quantity in the microscopy results that could suggest cell adhesion or proliferation modification.
Keywords: biomaterial; cytotoxicity; osteogenic cells; titanium alloys